Nonsteroidal anti-inflammatory drug use and endurance during running in male long-distance runners - da Silva, E.; Pinto, R. S.; Cadore, E. L.; Kruel, L. F. (Journal of Athletic Training, 2015)
Context: The effect of ibuprofen on pain tolerance during exercise is controversial, and its effects on endurance performance have been poorly investigated.